1998
DOI: 10.1164/ajrccm.157.4.9704134
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Adhesion Molecules in Cystic Fibrosis

Abstract: A marked influx of inflammatory cells occurs into the airways of patients with cystic fibrosis (CF), which may contribute to the development of lung injury. Leukocyte-endothelial adhesion molecules play a crucial role in the recruitment of inflammatory cells, and soluble forms of these molecules have been shown to increase in several inflammatory diseases. By using a capture ELISA, we determined serum levels of soluble ICAM-1 (sICAM-1), E-selectin (sE-selectin), and VCAM-1 (sVCAM-1) in patients with CF, in sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 33 publications
5
34
1
Order By: Relevance
“…Further studies are needed to characterize the expression of the counterligands of PMN from airways in its adhesion to airway epithelial cells. Our data showing that ICAM-1 is more expressed in cftr-deficient IB3-1 cells compared with C38 and BEAS-2B cells corroborates with other studies showing high ICAM-1 expression in the CFTE29o Ϫ cell line (⌬F508 homozygote tracheal epithelial cells) (22) and elevated soluble ICAM-1 levels in blood samples from CF patients (14).…”
Section: Discussionsupporting
confidence: 92%
“…Further studies are needed to characterize the expression of the counterligands of PMN from airways in its adhesion to airway epithelial cells. Our data showing that ICAM-1 is more expressed in cftr-deficient IB3-1 cells compared with C38 and BEAS-2B cells corroborates with other studies showing high ICAM-1 expression in the CFTE29o Ϫ cell line (⌬F508 homozygote tracheal epithelial cells) (22) and elevated soluble ICAM-1 levels in blood samples from CF patients (14).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, IL-8, in concert with ENA-78 and the GRO family, plays a vital role in the pathophysiology of inflammatory lung disease. These potent chemokines attract neutrophils to inflammatory sites, where their transepithelial passage is facilitated by ICAM-1 and their survival is prolonged by the hemopoietic cytokine GM-CSF (49,50). In this study both A46R and A52R were found to inhibit IL-1-and NE-induced GM-CSF up-regulation in bronchial epithelial cells.…”
Section: Discussionmentioning
confidence: 53%
“…Among the adhesion molecules up-regulated in the P. aeruginosa-infected airway is ICAM-1 (21,22). To our knowledge, our studies were the first to examine the effect of P. aeruginosa phenazines on ICAM-1 expression (20).…”
mentioning
confidence: 86%